Thermodynamic modeling and critical experiments on the Al-Fe-Nb system - Silva, Antonio Augusto Araujo Pinto da (2015)
The equilibrium diagrams are the starting point and the guideline to predict and control the microstructure that will form during processing materials. Despite experiments being necessary in binaries and ternaries systems, it is difficult to experimentally determine phase diagrams of higher orders systems over wide ranges of compositions and temperature. The CALPHAD (CALculation of PHAse Diagrams) method was developed in order to solve this problem. The essence is to optimize the parameters of thermodynamic models that describe the Gibbs free energies of each phase aiming to reproduce the experimental and estimated (abinitio) data. The compound energy formalism (CEF) is widely used in order to describe phases which present several sublattices. It allows the modeling of a large variety of phases and numerous methods have been developed to treat different situations. The activities in this work developed a new approach of the CEF (NACEF) based on a mathematic analysis of the parameters which leads to a new formulation of the Gibbs free energy function evolving new independent parameters in which new independent parameters are obtained to express the Gibbs free energy. This approach was used in this work to describe the intermetallic phases with two-sublattice in which the only defect type is anti-sites (A,B)a(A,B)b. The Al-Fe-Nb system was chosen due to its importance for the manufacturing process of several families of alloys currently used, e.g. steels, light alloys, and also for the development of new materials for high temperatures application. The binaries Al-Nb and Fe-Nb were reassessed and the Al-Fe-Nb system was assessed for the first time using literature information and new experimental data.